Catalytic effect of capital transfers in a federal context: The case of Spanish regions - Jaime Vallés-Giménez; Anabel Zárate-Marco (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
There is a broad theoretical consensus on the effects of transfers (desired incentive impacts and induced adverse effects). But, as the literature review shows, there is not an accepted methodology for the empirical evaluation of these effects. The authors suggest a simple but rigorous empirical approach to quantify the catalytic effect of conditioned transfers for investment and their asymmetric impact across regions in Spain. To identify this behaviour, they have applied different empirical approaches with frontier techniques that let them consider the frontier as a proxy for potential investment. The results show that the conditioned transfers received by the regions from higher levels of government have a stimulus effect for investments, especially in the poor regions. The authors identify several factors explaining this unbalanced catalytic effect: the political cost of tax collection, political factors, inadequate management of debt, and other variables such as the level of economic development, population density, and the economic cycle.
Keywords: H20; H54; H7; 330; catalytic effect; capital transfers; regional capital expenditure; frontier techniques